Contributions to the development of studies and practices in the area of health evaluation - Oliveira, Alcione Brasileiro; Bomfim de Souza, Mariluce Karla; Esperidião, Monique Azevedo (Revista Aval, 2023)
The pertinence of investing in training and qualification of professionals in the area of the health evaluation in Brazil can favor training and learning strategies that contribute to decision-making instances in the production of necessary information, aiming to improve the overall performance of the system, and contribute to the institutionalization field of evaluation in the health service system. In view of the insertion of professors in conducting actions aimed at the qualification of higher education professionals, this article, aims to analyze important theoretical and methodological aspects for the proposition and development of training actions in health monitoring and evaluation at undergraduate and Lato sensu levels. It is concluded that there is a strong demand for training in the area of the health evaluation, with the need for professional staff for health services, at different levels of the health system.